PERANAN PENDEKATAN ANDRAGOGIS DALAM PEMBELAJARAN PENDIDIKAN JASMANI - Guntur Guntur (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2009)
The dichotomy of physical education learning approach above is something interesting to be observed. Learning-centered teachers (teacher-centered learning) identified as a learning process that applies the principles of pedagogy, while learning-centered on student (student-centered learning) is a learning approach that applies the principles of andragogy. Pedagogical approach is more emphasis on efforts to transmit knowledge and skills of physical education in order to prepare students for life in the future. Instead, andragogy approach is more emphasis on guiding and helping students to find the experience, knowledge, skills and attitudes in order to solve the problems he faced. Some physical education learning activities that can be done through the role of andragogy learning which are: playing a role (role- plays), training (drilling) cooperation and communication in the motion task, the assignment (task) Keywords: Andragogy, Pedagogy, Physical education